(untitled) (Journal of Comparative & International Higher Education, 2023)
Women academics face unparalleled challenges such as underrepresentation and marginalization in Chinese higher education. A review of the literature revealed a tendency in the scholarly discussions that separates gender from the social and organizational processes, which is a missed opportunity to better understand how gender interacts with the broader social, cultural, and political contexts. Using three major organizational theory perspectives, this conceptual paper addresses the issue of academic gender disparity through analyzing organizational culture, organizational management, and the way higher education institutions interact with the external environments. Higher education institutions are gendered organizations that create, fortify, and reproduce gender inequalities. This essay will provide various methodological, epistemological, and ontological possibilities of interventions for transformative organizational change.